Wage policy patterns at the firm level: an analysis on Italian medium and large firms - Sgobbi, F. (2013)
This paper provides an empirical analysis of wage policy at the firm level. Based on cluster analysis applied to a sample of medium and large Italian firms and their employees, this paper classifies the wage policy patters adopted, outlines the drivers underpinning the identified patterns and provides preliminary evidence on the dynamics of wage policy at the firm level. The results of the empirical analyses show that identified wage policy patterns present a mix of hybrid characteristics rather than align with the ideal types of the internal and the external labour markets hypothesised in the literature. The wage policy models adopted by sampled firms display significant dynamic patterns between 1989 and 2004: 28.9% of the firms sampled in both years switch to a different wage policy pattern, with an overall increase of firms providing leading pay rates.